Model Pembinaan yang Holistik di Asrama bagi Mahasiswa Teologi - Setyo Utomo, Bimo; Tjondro, Eddy (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2022)
Dormitories in a theological education institution not only function to be a shelter for students, but also a place for students to learn from each other's respective regional cultures, learn to socialize, learn to train sensitivity or care, learn to obey and submit to the coaches, and become personal who has the character of Christ. In the field, it is undeniable that there are many problems, such as problems due to diverse student backgrounds, student discipline, student social interactions with the outside world, student adaptation patterns in various dormitories, and many other things. The methodology used in this research is descriptive and qualitative. Support from the Bible and several biblical sources are also presented in a systematic description according to the framework of thinking. From the results of the study, it was found that there were six formulations of student development models in theological institutions in dormitories that were holistic and ideal, namely (1) a spiritual-centered coaching model, (2) a transformative coaching model, (3) an integrative and holistic coaching model, (4) structured discipline model, (5) projective and anticipatory coaching model, and (6) teamwork coaching model.  AbstrakAsrama dalam sebuah institusi pendidikan teologi tidak hanya berfungsi untuk menjadi tempat penampungan mahasiswa saja, tetapi juga merupakan wadah mahasiswa saling belajar budaya daerah masing-masing, belajar bersosialisasi, belajar untuk melatih kepekaan atau kepedulian, belajar untuk taat dan tunduk pada pembina, serta menjadi pribadi yang memiliki karakter Kristus. Di dalam lapangan tidak dipungkiri terdapat banyak masalah, seperti misalnya permasalahan karena latar belakang mahasiswa yang beragam, kedisiplinan mahasiswa, interaksi sosial mahasiswa dengan dunia luar, pola adaptasi mahasiswa di asrama yang beragam, dan masih banyak hal lainnya. Metodologi yang digunakan dalam penelitian ini adalah kualitatif diskriptif. Dukungan dari Alkitab dan beberapa sumber pustaka juga dipaparkan dalam sebuah uraian sistematis sesuai dengan kerangka berpikir. Dari hasil penelitian, didapatkan enam rumusan model pembinaan mahasiswa di institusi teologi berasrama yang holistik dan ideal, yaitu (1) model pembinaan yang berpusat pada hal rohani, (2) model pembinaan transformatif, (3) model pembinaan integratif dan holistik, (4) model disiplin terstruktur, (5) model pembinaan proyektif dan antisipatif, serta (6) model pembinaan teamwork.